Uncommon T12 Burst Fracture after an Epileptic Crisis - Akiki Alian (Case Reports in Orthopedics)
People having an epileptic crisis present to the hospital with an altered mental status and generalised fatigue. The most common orthopaedic pathology associated to epilepsy is the undiagnosed posterior shoulder dislocation. These same patients often complain from back pain that is often neglected and misdiagnosed as muscular contracture following the epilepsy crisis. We describe here the case of a patient who presented after here epilepsy crisis with back pain. Investigations revealed an uncommon burst fracture that needed a surgical treatment. Conclusion. Back pain after an epileptic crisis should be investigated more seriously with an adequate clinical examination and a minimum of a radiography of the back.